(untitled) (Contrastive Linguistics, 2024)
Милена Йорданова, Ирина Саръиванова (съст.) 70 години специалност „Тюркология“ в софийския университет „Св. Климент Охридски“, София: УИ „Св. Климент Охридски“, 2022, 325 с. The purpose of this review is to describe the results of celebrating 70 years of the “Turkic and Altaic Studies” Department at Sofia University “St. Kliment Ohridski”. The collection presents research in the field of linguistics, literary studies, language teaching and didactology, history and cultural studies in the field of Turkic studies.